2014
DOI: 10.6061/clinics/2014(10)01
|View full text |Cite
|
Sign up to set email alerts
|

General anesthesia type does not influence serum levels of neutrophil gelatinase-associated lipocalin during the perioperative period in video laparoscopic bariatric surgery

Abstract: OBJECTIVES:Video laparoscopic bariatric surgery is the preferred surgical technique for treating morbid obesity. However, pneumoperitoneum can pose risks to the kidneys by causing a decrease in renal blood flow. Furthermore, as in other surgical procedures, laparoscopic bariatric surgery triggers an acute inflammatory response. Neutrophil gelatinase-associated lipocalin is an early and accurate biomarker of renal injury, as well as of the inflammatory response. Anesthetic drugs could offer some protection for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Our study found no significant difference between the two groups in post-operative creatinine levels. In a study with 64 patients who underwent bariatric surgery, Fernandes et al [20] determined acute kidney damage with neutrophil gelatinaseassociated lipocalin and found no significant difference between the TIVA and volatile anesthesia groups.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found no significant difference between the two groups in post-operative creatinine levels. In a study with 64 patients who underwent bariatric surgery, Fernandes et al [20] determined acute kidney damage with neutrophil gelatinaseassociated lipocalin and found no significant difference between the TIVA and volatile anesthesia groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although our aim was to focus on pneumoperitoneum as the only factor in the study, such limitations may explain the lack of difference for different pressure ranges. In a study using NGAL in patients undergoing bariatric procedures with mean pressure of 12 mm Hg and pneumoperitoneum lasting approximately 130 minutes, Fernandes et al found no significant changes in the biomarker [ 27 ], which suggests that short duration is a relevant factor.…”
Section: Discussionmentioning
confidence: 99%